Visual permeability in architectural design: Case: Hotel + Convention Center + Artisan Market with enhancement of the Monumental Environment - Salazar Fernández, Marusca Sonia (2020)
The present investigation arises from the concern of the current spaces, since they are closed and too many excluded from the exterior, so the topic of visual permeability is touched on as a type of solution for architectural design, since permeability allows the passage of the visual through different spaces, allowing you to have a better relationship between exterior and interior. The purpose of this research is to analyze how visual permeability is related to architectural design in order to achieve materials that present a certain porosity, that the shape allows light to enter and generates filters inside the building, in addition to spaces that have continuity and thus allow you have a better relationship with public and private spaces.